Predicting successful/unsuccessful extrapolation for in vivo total clearance of model compounds with a variety of hepatic intrinsic metabolism and protein bindings in humans from pharmacokinetic data using chimeric mice with humanised liver. (3rd May 2020) - Sawada, Takeshi; Yamaura, Yoshiyuki; Higuchi, Satonori; Imawaka, Haruo; Yamazaki, Hiroshi
Abstract: 1. Immunodeficient chimeric mice with humanised liver have been useful in predicting total clearance values of drugs in humans. However, their usefulness may currently be limited for specific compounds with interspecies differences. 2. In vivo total clearance and in vitro hepatic intrinsic clearance values of 16 model compounds were determined in control/humanised-liver mice and in mouse and human hepatocytes, respectively, for extrapolating the total clearance values of compounds in humans. 3. The predictability of in vivo total clearance values of 11 model compounds in humans was adequate using pharmacokinetic data from humanised-liver mice. The predictability of total clearance values using humanised-liver mice was better than conventional allometric scaling for compounds with large interspecies differences in in vitro hepatic intrinsic clearance or plasma unbound fractions. 4. There were trends that total clearance values in control and humanised-liver mice were similar to or higher than reported hepatic blood flow rates in normal mice among four compounds with poor predictability. Diazepam, with the poorest predictability, showed 38-fold-higher hepatic intrinsic clearance in mice than in humans. 5. These results could lead to guidelines describing that compounds may be suited or unsuited to extrapolating total clearance values in humans from pharmacokinetics in humanised-liver mice.